Inflectional forms in students’ writing: A point of view from morphological analysis - Amuntyastuti, Sekar; Sriati Usman; Bochari, Siska (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2023)
The objective of this study was to determine the most difficult and dominant inflectional form in students' writing as well as the variables that affect how difficult it is for students to comprehend the function of inflectional forms. This study examined inflectional markings in regular and irregular forms of content words. The design of this study was quantitative descriptive with a population taken from the 3rd-semester students of the English Education Study Program of Tadulako University who have enrolled Grammar subject. The sample of this study was 154 students of the 3rd-semesterÂ students by using a simple random sampling technique. The instruments to collect the data were a test and a questionnaire. The results of the data analysis show that: (1) the most difficult form of inflectional forms used by the students was suffix -est as superlative degree, (2) the most dominant form of inflectional forms used by the students was the suffix -ing as progressive marker, (3) there were two factors influencing the studentsâ€™ difficulty in using the function of inflectional forms which were internal factors. The test results indicate that students lack sufficient knowledge of tenses, as they are unable to apply the present, past, or past participle tenses.